PERSEPSI MAHASISWA TENTANG KOMPETENSI MENGAJAR DOSEN PENGAMPU PADA MATA KULIAH STRUKTUR ALJABAR - Naning Sutriningsih (Universitas Muhammadiyah Pringsewu, 2016)
Students perception about lecturer teaching ability of Aljabar Structural are observation process, introduction, conclusion, and student's assessment about lecturer ability in learning management includes, comprehension towards students, planning and learning implementation, learning outcome evaluation and student's development ability in several competence actualization. The importance to find out the students' perception of lecturer teaching competency by students' learning performance is 70% in Aljabar Structural subject during four year in low category. The objective of this study is knowing the students' perception about lecturer teaching. Competency in the Aljabar Structural subject students' perception data was gotten by questionnaire whereas the students' learning performance data was gotten from students' learning performance data was gotten from students' learning outcome that documented in BAAK STKIP MPL. Furthermore, from analysis the data perception got 75,6% by using descriptive, the students got the perception in good categorize and very good about students' competency of Aljabar Structural subject. It shown that students perception was not give significant contribution toward low students performance shown by contribution score 2,69%. Keywords: Students perception, students' learning performance, Aljabar Structural